2019
DOI: 10.11591/ijere.v8i4.20266
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-victimization and perceived depression: Serial mediation of self-esteem and learned-helplessness

Abstract: <p><span>Literature suggests that the perception of being cyber-victimized is a stronger predictor of depression symptoms than the perception of being victimized offline, and that learned-helplessness can explain the prediction of perceived cyber-victimization on perceived depression. Nevertheless, other studies suggested that the link between perceived cyber-victimized and learned-helplessness is weakened by state self-esteem. This study investigates the double mediation effect of state self-estee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
(103 reference statements)
1
15
0
Order By: Relevance
“…For example, Cohen et al [ 25 ] surveyed 505 Israel adolescents and found that victims who experienced a high level of self-blame were prone to have depression and suicide ideations. This was similar to an online survey carried out by Prihadi et al [ 26 ], where findings reported that both self-esteem and learned helplessness mediated the link between perceived cybervictimisation and perceived depression. Niu et al [ 17 ] also revealed in their study on 755 Chinese adolescents that psychological security was a mediator between cybervictimization and depression, but a growth mindset could significantly alleviate the adverse effects of cyberbullying victimization on psychological security and on depression.…”
Section: Introductionsupporting
confidence: 90%
“…For example, Cohen et al [ 25 ] surveyed 505 Israel adolescents and found that victims who experienced a high level of self-blame were prone to have depression and suicide ideations. This was similar to an online survey carried out by Prihadi et al [ 26 ], where findings reported that both self-esteem and learned helplessness mediated the link between perceived cybervictimisation and perceived depression. Niu et al [ 17 ] also revealed in their study on 755 Chinese adolescents that psychological security was a mediator between cybervictimization and depression, but a growth mindset could significantly alleviate the adverse effects of cyberbullying victimization on psychological security and on depression.…”
Section: Introductionsupporting
confidence: 90%
“…With the lockdown and SFH policies enforced, the usage and inclination towards SM were not only improved. SM became one of the most salient sources of social feedback, which means that the lockdown population was more exposed to and affected by more detailed information about the pandemic itself, including its social implication, fake news, hoaxes, and less-educated opinions [20], as well as perceived cyber-victimization [21], misinformation [22], and unhealthy social comparison [23], that led to negative way to accept [24]. These changes might affect some socio-psychological constructs such as how people perceived that they are supported by their society, how they matter to their society, fear of not being included or informed on what happens out there, and eventually, the way they evaluate whether their life is worth living.…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of this current study is to examine whether unconditional self-acceptance can explain the protective property of mattering on social comparison among undergraduate students in Malaysia. Social comparison tendency became our main context, because social comparison theory, suggested that it is our primary motive to learn and compare ourselves with those around us to define the self [1]; nevertheless, the current trend indicates that when university students have the tendency to compare themselves with others, in terms of academic achievement [2], physical appearance [3], or general life satisfaction [4], [5] they would likely to develop emotional difficulties and mental health issues, such as uncontrolled anger and depression [6], [7], especially if they lack of ability to accept themselves unconditionally. In other words, abilities to unconditionally accept oneself keep the levels of happiness and well-being, positive self-esteem and optimism, as well as protect individuals from depression and anxiety [8], [9].…”
Section: Introductionmentioning
confidence: 99%